The approximate solution of fractional Fredholm integrodifferential equations by variational iteration and homotopy perturbation methods - Kadem, Abdelouahab; Kilicman, Adem (Hindawi Publishing Corporation, 2012)
Variational iteration method and homotopy perturbation method are used to solve the fractional Fredholm integrodifferential equations with constant coefficients. The obtained results indicate that the method is efficient and also accurate.